Ancient dramatic chorus through the eyes of a modern choreographer : Zouzou Nikoloudi - Savrami, Katia (Cambridge Scholars Publishing, 2016)
This book critically analyses the work of Zouzou Nikoloudi, a major Greek choreographer (1917-2004), and the way she presented, with her company Chorica, the choral odes of ancient Greek drama, especially tragedy. It also sheds light on the theoretical underpinnings of Nikoloudi's choreographic work, the result of her own research on this central problem in contemporary performances of ancient Greek drama, particularly the manner in which the ancient Greek chorus may be revived. More specifically, the book provides answers to several key questions concerning Nikoloudi's work, namely: What were.